Development Of Laps-Based Plant Physiology Anatomy Practicum Module - Heuristic To Improve Students' Problem-Solving Skills - Tiya, Herditiya; Dafrita, Ivan Eldes (JURNAL PENDIDIKAN SAINS (JPS), 2023)
This research aims to determine the feasibility of the LAPS-HEURISTIC-Based Plant Anatomy and Physiology practicum module which was developed to improve students' problem solving abilities. This research is using research and development method adapted from Borg and Gall. The research subjects were students of the Biology Education Program at IKIP PGRI Pontianak who were taking Plant Anatomy and Physiology courses. The data collection tools used were module validation sheets, tests, and response questionnaires. The results showed that the developed module was declared very valid by media experts with an average validation of 91% and material experts with an average validation of 95%, very practical with an average response of 80%, and effective in improving problem solving abilities with an N-value Gain of 0.73 in the high category. In conclusion, this LAPS-HEURISTIC-Based Plant Anatomy and Physiology practicum module is proper to use.